Cerebral metastasis from adenocarcinoma of cervix: Metastasis cerebral de adenocarcinoma de cervix - Alzamora-Jiménez, Álvaro (2018)
Cervical cancer is the most frequent type of cancer in Peruvian women and in the population general. Cerebral metastases of the cervix are extremely rare with an incidence of 0.4 to 2.3% and only approximately 100 case reports in the medical literature. We report a case of a 52-year-old woman with a history of cervical cancer who after 14 months of this diagnosis presents headache, vomiting and upheaval of conscience. In the brain MRI study, evidence a contrast-enhancing lesion in the right parieto-occipital region. Craniotomy is performed minimal parietal with stereotactic assistance and complete resection of the tumor. According to the report of the Pathology service indicated metastasis of endocervical adenocarcinoma. The patient had a good postoperative evolution with remission of neurological symptoms.     DOI 10.25176/RFMH.v18.n4.1740